Developing Plant Ethnophysiology Flashcards to Support Contextual Learning of Photosynthesis Through Local Wisdom Integration - Mellisa Mellisa; Ibnu Hajar; Yandri Waltriandi; Riadatil Fitri; Thidarath Paladkong (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Science education in the 21st century requires innovative learning media that not only strengthen students’ conceptual understanding but also connect scientific knowledge with real life and cultural contexts. Integrating local wisdom into biology learning can provide meaningful learning experiences by linking abstract scientific concepts with students’ surrounding environments and traditional knowledge. In this context, ethnophysiology based learning media offer opportunities to support contextual and culturally responsive science instruction. This study aimed to develop plant ethnophysiology flashcards that integrate photosynthesis concepts with local wisdom to support students’ conceptual understanding, enhance learning engagement, and provide contextualized biology instruction grounded in local cultural knowledge. This study employed an educational Research and Development (R&D) approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. However, the development process in this research was limited to the Analysis, Design, and Development stages. Expert validation was conducted during the Development stage to evaluate the feasibility of the flashcards in terms of learning, media design, and material content, while the Implementation and Evaluation stages will be conducted in subsequent research. The validators consisted of learning experts, media experts, and subject matter experts. Data were collected using validation sheets and analyzed using a Likert scale. The validation results showed that the overall average validity score from the learning experts, media experts, and material experts was in the very valid category. Therefore, the flashcards were categorized as highly valid and suitable for use in biology learning. These findings indicate that plant ethnophysiology flashcards have strong potential as contextual learning media for strengthening students’ understanding of photosynthesis, increasing learning engagement, and fostering appreciation of local cultural knowledge.